Dynamic relationship between sector-specific indices and macroeconomic fundamentals / Jaafar Pyeman and Ismail Ahmad - Pyeman, Jaafar; Ahmad, Ismail (Accounting Research Institute (ARI) & Faculty of Accountancy, 2009)
This study focuses on the issue of long-run and short-run relationships between sector-specific indices of Bursa Malaysia and macroeconomic variables. The traditional variable under observation in analyzing stock market performance has been an aggregate stock market index. However, the application of an aggregate index could lead to misleading interpretation on the actual performance of each sector in Bursa Malaysia. Therefore, the main objective of this study is to analyze the dynamic properties of the relationship between sector-specific indices of Bursa Malaysia and macroeconomic variations. The sectoral indices of Bursa Malaysia selected for this study are namely, Construction, Plantation, Consumer Product, Finance, Industrial Product, Mining, Hotel, Property and Trading and Services. The macroeconomic variables are represented by real economic activity, interest rate, inflation rate, money supply and exchange rate. The monthly data series of the macroeconomic variables and stock market indices are obtained for the period from 1993 to 2006. This study has identified various trends of responses among the sector-specific indices towards the innovation in macroeconomic variables. The results suggest that unanticipated changes in macroeconomic variables could lead to similar patterns in some of the sector-specific indices with the effects differing mainly in terms of speed of adjustments towards equilibrium level in the long-run.